Development of dense void-free electrospun SPEEK-Cloisite15A membrane for direct methanol fuel cell application: Optimization using response surface methodology. (19th October 2017) - Awang, N.; Jaafar, Juhana; Ismail, A.F.; Othman, M.H.D.; Rahman, Mukhlis A.; Yusof, N.; Aziz, F.; Salleh, W.N.W.; Suradi, S.S.; Ilbeygi, H.; Wan Mohd Noral Azman, W.N.E.; Arthanareeswaran, G.
Abstract: Response surface methodology (RSM) was utilized to design the experiments at the settings of solution concentration, voltage and the collector distance. It also imparted the evaluation of the significance of each parameter on the resultant physico chemicals (proton conductivity, methanol permeability and water uptake). The investigations were carried out in the two-variable process domains of several collector distances as applied voltage and the solution concentration were varied at a fixed polymer molecular weight. The result showed that all three factors were found statistically significant in the production of void free electrospun SPEEK/Cloisite membrane. All responses were correlated to these variables by using a second order polynomial function. The optimum condition for void free electrospun SPEEK/cloisite was at 0.17 wt% concentration with applied voltage of 22.15 kV and 18.83 cm distance from needle tip to screen collector. Highlights: Electrospinning parameters are optimized using Response Surface Methodology (RSM) from Design Expert 6 (DX6) software. All of electrospinning parameters are found statistically significant in producing PEMs for DMFC. Exfoliated structure is important in improving membrane physico chemical properties.